As figurações do pária: sujeitos (in)visíveis em contos de João Melo - Silva, Paloma Argemira da (2018)
This research aims to analyze some stories by the Angolan fiction writer João Melo, focusing on (in)visible subjects included in the pariah category (VARIKAS, 2014). Being one of the singular cases in the African Literature of Portuguese Language, the writer published poetic works and has been emphasizing like a representative author of short stories, with plots related to social conflicts, as well as the ones of gender, besides weaving a critical reflection on political and historical aspects of Angola. The research will focus on the following short stories ―O discurso da beleza‖, ―O criador e a criatura‖ and ―Maria‖. We are interested in investigating in the texts the aspects of the fictional representation of essentially politicalsocial themes, such as the clash with chauvinism, violence and the lack of identity of the country, generating suffering and conflicts. Throughout the analyzes, we will try to verify to what extent these aspects contribute to the identity construction of the Angolan subject.